2021
DOI: 10.1016/j.jtumed.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among patients with psoriasis: A correlation with quality of life and associated factors

Abstract: Objectives Psoriasis is a chronic, immune-mediated illness that primarily affects the skin, nails and joints. This illness may predispose people to mental disorders such as depression and anxiety. This study aims to determine the prevalence of depression and anxiety in patients with psoriasis and their correlation with quality of life and associated factors. Methods This cross-sectional study involved 174 patients with psoriasis at the dermatology clinic of Hospital Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…In this study, we found that the prevalence of depression among patients with severely impaired QOL was almost 19%, with a mean score of 6.72 (SD 4.412). A recent study at a similar site using the Hospital Anxiety and Depression Scale (HADS) to assess depression found about 8.5% of patients had depression [ 29 ]. Generally, the proportion of psoriasis patients with depression symptoms ranged from 9% to 55%, likely due to differences in the screening methods and study populations [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the prevalence of depression among patients with severely impaired QOL was almost 19%, with a mean score of 6.72 (SD 4.412). A recent study at a similar site using the Hospital Anxiety and Depression Scale (HADS) to assess depression found about 8.5% of patients had depression [ 29 ]. Generally, the proportion of psoriasis patients with depression symptoms ranged from 9% to 55%, likely due to differences in the screening methods and study populations [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the psychological stress might worsen the severity of psoriasis. A cross-sectional study reported anxiety in approximately 17% of psoriasis patients and a positive correlation with the dermatology life quality index (DLQI) [57]. In this study, an EPM test was performed to evaluate anxiety-like behavior in psoriasis mice and the beneficial effects of coptisine.…”
Section: Discussionmentioning
confidence: 99%
“…A larger study investigating depression and anxiety in psoriasis patients revealed that 8.5% of patients had depressive symptoms and 16.9% had anxiety symptoms, lesions on the lower limbs and dyslipidemia being associated with depression in the studied population. 7 Another study comparing the prevalence of emotional disorders in patients diagnosed with psoriasis revealed that overall, patients with psoriasis were more likely to develop depression compared to the control group, whereas late-onset psoriasis was associated with both anxiety and depression. 8 Overall, the prevalence of psychiatric conditions in psoriasis is suggested to be in the range of 24-90%, with the same authors concluding that psychiatric disorders tend to be underdiagnosed in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%